HANNAH ARENDT’S “POLITICAL BEINGS” AS A REPRESENTATION OF POLITICAL EXISTENTIALISM FOR HUMANS EXISTING IN THE WORLD - Lustanto, Rendi; Kartika, Ganang Dwi (International Review of Humanities Studies, 2019)
Discussions in politics often focus on a broad range of political systems or political movements. This focus leads to the efforts to direct the public to the conversation of "Politics" in the sense of a system and it overlooks the fact that politics is built on the crystallization of ideas from individuals who interpret the condition of togetherness in the world. The interpretation is very important because it is the starting point for political discourse to grow and develop, which is often referred to as individual’s "political" struggle. The struggle involves a conversation between me and myself which is later embodied into an individual political idea. The effort to uncover the importance of "politics" within the framework of individual struggle becomes very important when the discourse provided by "Politics" reaches an impasse. This condition gives an impact on the quality of "Politics" that can cause a significant decline, that is "Politics" is not interpreted to achieve justice but only as a means of pursuing mere interests. This study applies qualitative methods based on theoretical and literary studies on Hannah Arendt’s existentialism, namely Vita Activa theory. The expected result of this study is to reconstruct the political concepts on the individual level that are necessary for human beings to be in the world.